1982
DOI: 10.1111/j.1469-8137.1982.tb03312.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF REDUCED SOIL MOISTURE AVAILABILITY ON LEAF MORPHOLOGY AND IN VITRO DRY MATTER DIGESTIBILITY OF FESTUCA ARUNDINACEA GENOTYPES WITH CONTRASTING LEAF TENSILE STRENGTH

Abstract: SUMMARYTwelve genotypes of Festuca arundinacea Schreb. differing in leaf size and leaf tensile strength were grown in pots with either adequate or very restricted watering. When leaves expanded under moisture stress their length, width, specific leaf area (SLA) and tensile strength were reduced but leaf dry wt was unaffected. However, the reduction in SLA was inversely proportional to original leaf strength. Leaf tensile strength was directly related to leaf length, SLA and mesophyll cell wall thickness. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Buxton and Casler (1993) reviewed this subject and suggested that: (i) long-term unconscious selection has led to decreased nutritive value of forage crops due to emphasis on yield and vigor traits, and (ii) increased forage nutritive value, if accomplished by reducing the concentration of cell wall constituents such as lignin or phenolics, may lead to reduced pest resistance. On the other hand, selection for reduced leaf cellulose concentration or tensile strength, both associated with increased IVDMD, led to increased tolerance to freezing and drought (Lancashire et aI., 1977;Silcock & Wilson, 1982;Wilson, 1981). Silcock and Wilson (1982) speculated that greater cell wall flexibility may be partially responsible for both increased drought and freezing tolerance.…”
Section: Forage Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Buxton and Casler (1993) reviewed this subject and suggested that: (i) long-term unconscious selection has led to decreased nutritive value of forage crops due to emphasis on yield and vigor traits, and (ii) increased forage nutritive value, if accomplished by reducing the concentration of cell wall constituents such as lignin or phenolics, may lead to reduced pest resistance. On the other hand, selection for reduced leaf cellulose concentration or tensile strength, both associated with increased IVDMD, led to increased tolerance to freezing and drought (Lancashire et aI., 1977;Silcock & Wilson, 1982;Wilson, 1981). Silcock and Wilson (1982) speculated that greater cell wall flexibility may be partially responsible for both increased drought and freezing tolerance.…”
Section: Forage Nutritional Valuementioning
confidence: 99%
“…On the other hand, selection for reduced leaf cellulose concentration or tensile strength, both associated with increased IVDMD, led to increased tolerance to freezing and drought (Lancashire et aI., 1977;Silcock & Wilson, 1982;Wilson, 1981). Silcock and Wilson (1982) speculated that greater cell wall flexibility may be partially responsible for both increased drought and freezing tolerance.…”
Section: Forage Nutritional Valuementioning
confidence: 99%